Investigating public awareness on circular economy in western China: a case of Urumqi Midong - Guo, Bin; Geng, Yong; Sterr, Thomas; Zhu, Qinghua; Liu, Yaxuan (Journal of cleaner production, 2017)
Facing the challenge of both resources scarcity and environmental pollution, Circular Economy (CE) has been adopted by the Chinese central government as a national development strategy for pursuing sustainable development. Behaviors and lifestyles play a vital role in achieving sustainable development. However, few studies were conducted on investigating consumers' behaviors and lifestyles. Consequently, it is necessary to conduct questionnaire surveys to understand public awareness and performance, as well as related progress, so that the barriers on CE implementation can be identified. Particularly, as a minority administrative region, Xinjiang is facing more challenges on promoting circular economy due to economic, cultural and language barriers. In order to provide more valuable policy implications to other Chinese regions with more minority residents, two questionnaire surveys were carried out in the Midong district of Urumqi city (the capital of Xinjiang), respectively in 2008 and 2013, covering responses from 418 interviewees. The results show that, while residents' understanding toward sustainable development increased from 10.1% in 2008 to 57.5% in 2013, only 41% of the interviewees knew the concept of circular economy, indicating residents' limited understanding on CE development. In addition, only 58.5% of the interviewees thought that wastes could be recycled in 2013, and residents were still facing the uncertainty of responsibility and the lack of knowledge for wastes separation. Moreover, around 80% of the respondents supported and recognized the importance of water saving and energy efficiency, and most of them would like to purchase water-saving and energy efficient appliances. With regard to people's CE behaviors, more respondents separated wastes in 2013 than in 2008, and waste items that have higher economic values were mostly separated. More than 94% of the respondents reused water and more than 80% of the respondents used energy-saving lamps at home. Less than 54% of the respondents utilized shopping bags for their shopping. Policy implications suggest that local governmental agencies should 1) introduce CE related knowledge and best practices to the public; 2) establish CE websites or information platform for public participation; 3) implement CE related policies; 4) provide preferential policies to the green products producers.